Anti-inflammatory Effects of Canthin-6-one Alkaloids from Ailanthus altissima - Cho, Seung-Kye; Jeong, Miran; Jang, Dae Sik; Choi, Jung-Hye (Planta Medica, 2018)
Canthin-6-one (CO) alkaloids possess various biological activities, including antibacterial, antitumor, antifungal, and antiviral activities. However, their anti-inflammatory effects and underlying molecular mechanisms are poorly characterized. This study aimed to investigate the anti-inflammatory effects of CO and its derivative 5-(1-hydroxyethyl)-canthin-6-one (5-HCO), isolated from the stem barks of Ailanthus altissima in lipopolysaccharide (LPS)-stimulated macrophages. CO (1 and 5 µM) and 5-HCO (7.5 and 15 µM) significantly inhibited the LPS-induced expression of inducible nitric oxide synthase. In addition, CO (1 and 5 µM) and 5-HCO (15 µM) markedly suppressed the production of prostaglandin E2 (PGE2) and expression of cyclooxygenase-2, a key enzyme in PGE2 synthesis, in LPS-stimulated macrophages. Moreover, CO treatment significantly reduced monocyte chemotactic protein-1 (MCP-1) and tumor necrosis factor-α (TNF-α) expression, whereas 5-HCO inhibited MCP-1, but not TNF-α expression. Both CO and 5-HCO inhibited the phosphorylation of inhibitor kappa B and transcriptional activation of nuclear factor kappa B (NF-κB) in LPS-stimulated macrophages. In addition, CO, but not 5-HCO, markedly reduced Akt phosphorylation. Taken together, these data suggest that CO, but not 5-HCO with a hydroxyethyl moiety on the D ring, has potent anti-inflammatory activity in LPS-stimulated macrophages through the downregulation of both the NF-κB and the Akt pathway.
Keywords: Ailanthus altissima; Simaroubaceae; alkaloids; canthin-6-one; 5-(1-hydroxyethyl)-canthin-6-one; inflammation; NF-κB